Don Quixote or Robin Hood: Minority Shareholder Rights and Corporate Governance in Korea - Lee, Boong-Kyu (Columbia Journal of Asian Law, 2002)
On December 27, 2001, in a derivative suit brought by the minority shareholders of Samsung Electronics against 11 current and former directors, a court of first impression awarded damages of W97.7 billion. If confirmed by the appellate Seoul High Court and ultimately the Supreme Court, the individual defendants must repay W97.7 billion to Samsung Electronics – but of course, since this is a derivative suit, the minority shareholder plaintiffs will not be compensated directly! The Samsung verdict represents the second pro-shareholder derivative verdict since the one in 1998 against Korea First Bank, but in monetary terms the recent decision dwarfs the W40 billion awarded in the latter case.2 It represents a major vindication of minority shareholder rights for good corporate governance and has been praised as a enlightened decision that takes away from the controlling owners what should be rightfully that of the shareholders as a whole. A “Robin Hood”-like imperative of sorts.